2016
DOI: 10.1016/j.cell.2016.10.052
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Epidermal to Dendritic T Cell Signaling Slows Wound Repair in Aged Skin

Abstract: SUMMARY Aged skin heals wounds poorly, increasing susceptibility to infections. Restoring homeostasis after wounding requires the coordinated actions of epidermal and immune cells. Here we find that both intrinsic defects and communication with immune cells are impaired in aged keratinocytes, diminishing their efficiency in restoring the skin barrier after wounding. At the wound-edge, aged keratinocytes display reduced proliferation and migration. They also exhibit a dampened ability to transcriptionally activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
220
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 205 publications
(231 citation statements)
references
References 53 publications
11
220
0
Order By: Relevance
“…Moreover, using an assay that specifically measures keratinocyte migration (Extended Data Fig. 2f), we found that keratinocyte outgrowth from ex vivo explants post-inflammation 13 was more robust than controls (Fig. 1g).…”
Section: Enhanced Wound Healing Post-inflammationmentioning
confidence: 92%
See 1 more Smart Citation
“…Moreover, using an assay that specifically measures keratinocyte migration (Extended Data Fig. 2f), we found that keratinocyte outgrowth from ex vivo explants post-inflammation 13 was more robust than controls (Fig. 1g).…”
Section: Enhanced Wound Healing Post-inflammationmentioning
confidence: 92%
“…Following a full-thickness wound, re-epithelialization is mediated by sensitized epidermal EpSCs, which transiently express K17 13 . Inflammation-experienced skin displayed enhanced epidermal thickness and accelerated re-epithelialization, but showed similar proliferation rates (Fig.…”
Section: Enhanced Wound Healing Post-inflammationmentioning
confidence: 99%
“…Immunofluorescence analyses of back skin and intravital videomicroscopy of ear skin shows that the process begins at ~12 hr post wounding with migration rates being highest (~1.6 µm/day) at the wound edge by day 3 (Aragona et al, 2017; Keyes et al, 2016; Park et al, 2017). By contrast, in a fashion similar to that seen in closure of the embryonic epidermis over the eyelid (Heller et al, 2014), the proliferative response occurs in the region behind and only partially overlapping with the migrating epidermal front (Park et al, 2017).…”
Section: Contribution and Dynamics Of Skin Stem Cells During Homeostamentioning
confidence: 99%
“…Regarding expression of homing and adhesion molecules of tissue-resident memory T cells, the γδ T cells from LNs of d28 IL-1β -/-mice had substantially decreased expression of CCR4 and significant but subtle differences in expression of CD103 and CLA compared with that in naive IL-1β -/-mice (Supplemental Figure 7). Finally, it is unclear whether the TCR signaling in the γδ T cells was required for protection; however, the butyrophilin family members (e.g., Skint1, Skint3, or Skint9) have recently been implicated as TCR ligands or costimulatory molecules for DETCs, which express the same CDR3 aa sequence (59,60). There was a significant correlation between reads encoding for the top γδ CDR3 sequences and BTLN2 (but not SKINT1, SKINT3, or SKINT9) in the LNs of d28 IL-1β mice (Supplemental Figure 8), suggesting that Btnl2 might activate the protective γδ T cells in our model.…”
Section: Trgj1*01mentioning
confidence: 99%